IAIN CURUP STUDENTS’ SELF-ENDURANCE AND PROBLEMS IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Muhamad Uyun; Idi Warsah (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The transformation of learning from offline to online modes due to the Covid-19 pandemic has affected students’ self-endurance in learning and the complexities of learning problems. Accordingly, this study was oriented towards investigating IAIN Curup students’ self-endurance and the problems they faced during online learning. Grounded in a qualitative method, this study incorporated 20 IAIN Curup students selected purposively as the participants. They were interviewed on the basis of the study’s foci. The data of interviews were analyzed using an interactive model. The findings demonstrated weak students’ self-endurance in online learning. Psychologically, they felt under pressure. Physically, their eyes’ condition got worse, and a few of them suffered from headache. They were psychologically bored as well less-concentrated, and they could not enjoy learning due to the limitation of social engagement in learning. Subsequently, as regards the problems faced during online learning, they had problems related to Internet’s signals, budgeting for fulfilling Internet’s needs, and difficulty in the search of learning resources, wherein the foregoing was categorized as a case of weak technological competence.